Immigration policies and the ecuadorian exodus - Simone Bertoli; Jesús Fernández-Huertas Moraga; Francesc Ortega (Institute for the Study of Labor (IZA), 2010)
Ecuador experienced an unprecedented wave of international migration since the late 1990s, triggered by a severe economic and financial crisis. This paper gathers individual-level data from Ecuador and the two main destinations of Ecuadorian migrants: the US and Spain. First, we provide a careful description of the main characteristics of migration flows, both in terms of their scale and skill composition. Second, we estimate Mincer regressions for Ecuadorians in the three countries, and attempt to reconcile the features of migration flows with our predictions for earnings by destination. We find that earnings differences can account for the higher share of college graduates among migrants to the US, but fail to explain the larger scale of the flows to Spain. We argue that the puzzle is explained by taking into account that (i) the options to migrate legally to either destination were slim, and (ii) the cost of illegally migrating to Spain was lower than to the US.
Keywords: O15; J61; D31; 330; Migration; selection; sorting; immigration policies; Internationale Wanderung; Auswanderung; Qualifikation; Ecuador; Einwanderung; Einwanderungsrecht; USA; Spanien